87 fs CEP-stable Cr:ZnSe laser system. (22nd January 2018) - Komm, Pavel; Sheintop, Uzziel; Noach, Salman; Marcus, Gilad
Abstract: A hybrid laser scheme for the generation and amplification of mid-IR ultrashort pulses, with a carrier to envelope stable phase, is presented. Seed mid-IR pulses with picojoule energies are obtained via intrapulse difference frequency generation from an 8 fs Ti:sapphire oscillator. The energy of these seed pulses is then amplified in a multipass Cr:ZnSe laser amplifier to more than a nanojoule/pulse level. The duration of the amplified impulses is measured to be 87 fs, and the width of their spectrum supports their compression to 50 fs.